Game Production Studies (Amsterdam University Press, 2021)
Video games have entered the cultural mainstream and in terms of economic profits they now rival established entertainment industries such as film or television. As careers in video game development become more common, so do the stories about precarious working conditions and structural inequalities within the industry. Yet, scholars have largely overlooked video game production cultures in favor of studying games themselves and player audiences. In Game Production Studies, an international group of established and emerging researchers takes a closer look at the everyday realities of video game production, ranging from commercial industries to independent creators and cultural intermediaries. Across sixteen chapters, the authors deal with issues related to labour, game development, monetization and publishing, as well as local specificities. As the first edited collection dedicated solely to video game production, this volume provides a timely resource for anyone interested in how games are made and at what costs.